Communities of innovation for climate change adaptation and disaster risk reduction: niche creation and antecipation - López-Gunn, Elena (2021)
This paper presents the concept of communities of innovation for climate change adaptation and disaster risk reduction. The paper discusses the added value of these types of communities to help address uncertain futures from the impact of climate change, which are highly context dependent. The paper frames these communities of innovation as part of innovation ecosystems in order to reflect on their key elements and added value. We argue that climate change and disaster risk management responses need to meet the needs of those experiencing problems with those that can offer solutions in distinct localities, including those that could fund or finance potential innovative solutions. Developing communities of innovation with the specific task of anticipating and creating niche solutions has been gaining traction in the EU. Some developed under the H2020 BRIGAID project are analysed here for other emergent COIs, as future-oriented communities tasked with the challenge to reduce disaster risks and enhance the climate resilience in their own spaces. This paper reflects on the experience of participants in these communities and their reflections and experience on whether these offer a useful form of organisation to anticipate future challenges, create niche solutions, and bring innovations to the market. The paper concludes with how communities of innovation can contribute to niche design and narratives of change to help achieve social and environmental resilience to reframe and help transition and transform current systems into more resilient, future-oriented communities